Crop type influences soil aggregation and organic matter under no-tillage - Martins, Marcio dos Reis [UNESP]; Cora, Jose Eduardo [UNESP]; Jorge, Ricardo Falqueto [UNESP]; Marcelo, Adolfo Valente [UNESP] (Elsevier B.V., 2009)
The adaptation of no-tillage system in tropical regions depends on the suitable choice of summer and winter crops which should contribute to improvement of soil properties. The aim of the present study was to determine the effect of crop sequences on soil aggregation and contents of organic C and polysaccharides in aggregates of a Rhodic Eutrudox under no-tillage. The treatments consisted of the combination of four summer crop sequences and seven winter crop sequences. The summer crop sequences were: maize monocrop (Zea mays L.) (MM); soybean monocrop (Glycine max (L) Merrill) (SS); crop sequence of soybean/maize/soybean/maize (SM); crop sequence of rice (Oryza sativa L.)/bean (Phaseolus vulgaris L.)/cotton (Gossypium hirsutum L.)/bean (RB). The winter crops were: maize, sunflower (Helianthus annuus L.). radish (Raphanus sativus L.), pearl millet (Pennisetum americanum (L.) Leeke), pigeon pea (Cajanus cajan (L.) Millsp), grain sorghum (Sorghum bicolor (L.) Moench) and sunn hemp (Crotalaria juncea L.). The highest total organic C, total polysaccharides and dilute acid-extracted polysaccharides contents were found in 2.00-1.00 mm water-stable aggregates and the lowest contents were found in <0.25 mm aggregates. The maize monocrop provided the highest water-stability of soil aggregates. This crop sequence provided the highest content of total organic C and dilute acid-extracted polysaccharides in aggregates with diameter of 6.30-2.00 mm. This indicates that the influence of crops on the stability of aggregates is mediated by total organic C and easily hydrolysable polysaccharides (polysaccharides other than cellulose) in the soil. There were no differences among effects of the winter crops (maize, sunflower, oilseed radish, pearl millet, pigeon pea, grain sorghum and sunn hemp) on the soil aggregation. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Soil aggregation; Soil carbohydrates; Soil structure; Crop rotation; Cover crops